2005
DOI: 10.1158/0008-5472.can-05-1162
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Paclitaxel Is Proportional to Cellular Total Antioxidant Capacity

Abstract: Paclitaxel, one of the most commonly prescribed chemotherapeutic agents, is active against a wide spectrum of human cancer. The mechanism of its cytotoxicity, however, remains controversial. Our results indicate that paclitaxel treatment increases levels of superoxide, hydrogen peroxide, nitric oxide (NO), oxidative DNA adducts, G 2 -M arrest, and cells with fragmented nuclei. Antioxidants pyruvate and selenium, the NO synthase inhibitor N W -nitro-L-arginine methyl ester, and the NO scavenger manganese (III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
175
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(188 citation statements)
references
References 28 publications
12
175
0
Order By: Relevance
“…CBS activity depends on the cellular redox state and is inhibited by NO or acidosis [46] and activated by ROS [45]. The balance between NO and ROS levels was shown as an important mechanism of the response to paclitaxel at low concentration [13,46]. In this study, at low dose of DTX, we found blockade of CBS as well as acidosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…CBS activity depends on the cellular redox state and is inhibited by NO or acidosis [46] and activated by ROS [45]. The balance between NO and ROS levels was shown as an important mechanism of the response to paclitaxel at low concentration [13,46]. In this study, at low dose of DTX, we found blockade of CBS as well as acidosis.…”
Section: Discussionsupporting
confidence: 60%
“…DTX was shown to interrupt the normal mitotic process through the disruption of microtubules [6], to have antiangiogenic effect [7], to activate several apoptotic cellular signals such as protein kinases and caspases [8,9], and to decrease structural and antioxidative gene expression [10,11]. Reactive oxygen and nitrogen species have been reported to be involved in taxane cytotoxicity [12,13], resulting from activation of NADPH oxidase [14]. Also DTX increased inducible nitric oxide synthase (iNOS) expression [15] and subsequent nitric oxide (NO) production [16] in breast cancer cells and through the stimulation of p38 activity in alveolar macrophages [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both classes of these drugs are able to generate ROS production in cancer cells, and ROS was found to be involved in DOX-and PTXinduced cell death in vitro and in vivo (Conklin, 2004;Ramanathan et al, 2005;Alexandre et al, 2006). Therefore, it was of interest to determine whether MnSOD could inhibit their ability to induce apoptosis.…”
Section: Expression Of Mnsod Confers Resistance To Drug-induced Apoptmentioning
confidence: 99%
“…We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103]. One final common pathway activated by the otherwise chemically heterogeneous group of molecules, such as chemotherapeutic agents, is the production of oxidative stress in different tissues and cells [147,148] and, through this effect they can potentially activate and/or sensitize the TRPA1 channel. Our recent works [103,146], however, indicated that oxaliplatin and paclitaxel do not directly gate TRPA1, as they do not cause any calcium response in primary culture of mouse or rat DRG neurons.…”
Section: Trpa1mentioning
confidence: 98%